Emergency remote teaching environment: a conceptual framework for responsive online teaching in crises - Whittle, Clayton; Tiwari, Sonia; Yan, Shulong; Williams, Jeff (Information and learning science, 2020)
Purpose This study aims to provide an educational framework for not only the emerging COVID crisis but also future emergency remote teaching environments (ERTE). Design/methodology/approach Using participatory design methodologies, this study engages K-12 teachers and professional instructional designers in a design-focused discussion. Findings This work identifies thematic elements present across multiple subject areas, school districts, learner ages and socio-economic situations. Using these themes, as well as design solutions created by our participants, the authors propose the ERTE framework. Research limitations/implications The framework presented is grounded in the experiences of a limited number of teachers, but presents a theoretically grounded approach to teaching in an emergent field. Practical implications This framework is designed for practical application for use by teachers operating in ERTE. Originality/value Though multiple online teaching frameworks exist, the ERTE framework is novel in its emphasis on shifting constants and variables rather than planned pedagogy and is specifically for use in unplanned or responsive remote teaching situations.